Brain Injury as the Result of Violence: A Systematic Scoping Review. Issue 3 (12th December 2016) - Bates, Annerley; Matthews, Sarah; Simpson, Grahame; Bates, Lyndel
ABSTRACT: This scoping review investigated risk factors, impacts, outcomes, and service implications of violence-related traumatic brain injury (TBI) for individuals and their informal caregivers. A systematic search (Web of Science, PubMed, PsycInfo, ProQuest, Medline, Informit; 1990–2015) identified 17 studies meeting the inclusion and exclusion criteria. Violence was the cause of between 3% and 26% of all TBIs. Males, a non-White racial background, preinjury unemployment, and preinjury substance abuse problems all elevated the risk for sustaining a violence-related TBI compared to other-cause TBI. However, few differences were observed in 12 months postinjury outcomes. No studies investigated the impact of violence-related TBI on informal caregivers.